Occurrence of the nan1 gene and adhesion of Pseudomonas aeruginosa isolates to human buccal epithelial cells - Wolska, Katarzyna; Kot, Barbara; Mioduszewska, Halina; Sempruch, Cezary; Borkowska, Lidia; Rymuza, Katarzyna (Biological Letters, 2013)
This study shows an association between the frequency of the nan1 gene (encoding neuraminidase) among 62 clinical Pseudomonas aeruginosa isolates and adhesion of these bacteria to human buccal epithelial cells. The 52 strains in which the gene was present (83.9%) were characterized by a higher adhesiveness (the mean number of adhering bacteria was 23.51 per cell) than strains in which the gene was not detected (16.23 per cell) and the difference was significant (P = 0.009, Mann-Whitney U test). Thus we found that the nan1 gene may play a role in the binding of clinical P. aeruginosa strains to buccal cells.